RANCANG BANGUN SISTEM PENGENDALI LAMPU RUANGAN BERBASIS PENGOLAHAN CITRA DENGAN METODE TEMPLATE MATCHING - , FITRI HANDAYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Uncontrolled electricity consumption will directly impact on the sustainability of natural resources used to generate it. Sparing in use of the electrical energy is one way to save the environment. Conventional switch in the room lighting system has a drawback of controlling the lamp due to the dependency of the human interaction. It leads to an ineffective and inefficient the use of the energy. This final project proposes a solution of controlling the lamp in a room. It based on the image processing method named template matching for detecting the presence of and absence of persons sitting on the chairs. Each chair is tagged by a marker as an image object that will detected. The room is divided into several areas of detections (Region of Interest) in order to focusing the search of a tag marker. If a tag is detected, it means there is no one sitting on the chair, then it will trigger the lamp driver to turn off the lamp, otherwise, it means there is someone sitting on the chair, the lamp driver will turn on the lamp. The result of this final project contributes to develop the green environment specially for the efficiency of the electricity consumtion on the room lighting system.